Growth and physiology responses of Samanea saman inoculated with arbuscular mycorrhizal fungi in silica post-mining soil media using biodegradable pots - Harus, Johanes S; Budi, Sri Wilarso; Sukendro, Andi; Mansur, Irdika (Brawijaya University, 2024)
Arbuscular mycorrhizal fungi (AMF) and biodegradable pots are environmentally friendly and enhance plant growth in adverse soil conditions. These studies explored AMF interactions and biodegradable pots in physiology, growth, and the uptake of nutrients in Samanea saman seedlings. The present research interactive effects of biodegradable pots with different compositions and raw material sizes with and without AMF inoculation on S. saman grown in silica post-mining soil media. Results indicated AMF inoculations significantly improved leaf chlorophyll content, photosynthetic rate, heights, diameters, biomass, as well as nutrient absorption of S. saman as compared with non-inoculated plants in biodegradable pots. AMF and biodegradable pots composed of 15% used newspaper, 70% compost, 5% cocopeat, and 10% rock phosphate showed the best results and increased the leaf chlorophyll content, photosynthesis rate, height, diameter, and total biomass of the plants by 161.1%, 208.7%, 263.6%, 118.1%, and 269.9%, respectively, compared to biodegradable pots composed only of used newspaper. Additionally, uptake of the nutrients nitrogen, phosphate, potassium, and magnesium increased by 365%, 800%, 369%, and 250%, respectively. By the fourteenth week after transplanting, the C/N ratio of the organic pot decreased significantly. Thus, AMF and biodegradable pots containing compost and rock phosphate interact positively and enhance the growth of S. saman under adverse soil conditions. These findings suggest that biodegradable pots containing compost and rock phosphate show potential as more environmentally friendly replacements for plastic bags (polybags) as growth medium containers for seedling production.